Studi tentang Motivasi ARMY Jakarta dalam Membeli Merchandise Idola (Studi Kasus Kaos Uniqlo X BT21) - Johanna Ruthllianie; Diah Ayu Candraningrum (Prologia, 2020)
This research attempts to adopt the individual motivation behind the decision in purchasing an idol merchandise. In addition the resources focused on the concept of consumer motivation and the consumer decision making process. The concept of motivation includes sources of motivation, divided into motivational intrinsic and motivation extrinsic. While the consumer decision-making process is divided into five steps which are recognized the need, looking for information, evaluation of decision, buying decision, and the consumer behavior after purchasing. The researcher uses a case study of the shirt Uniqlo X BT21 with qualitative method. The results of the research which is the consumer motivation lead to purchasing a Uniqlo X BT21 shirt. Parasocial interaction in fact can influence consumers to purchase merchandise. The more closely the relation between society can lead to higher motivation to purchase the needs. The collaboration between Uniqlo and BTS succeeds in attracting the fans. The results of collaboration between brand and public figures now is a strategy for creating promotional products. Entrepreneurs, who also use this strategy need to see the opportunity by using this phenomenon. Penelitian ini mengangkat tentang motivasi individu dalam keputusan pembelian merchandise idola. Konsep yang digunakan yaitu motivasi dan keputusan pembelian. Konsep motivasi meliputi sumber motivasi, yaitu melalui motivasi intrinsik dan motivasi ekstrinsik. Sedangkan untuk keputusan pembelian melalui lima tahapan yaitu, mengenali kebutuhan, pencarian informasi, evaluasi alternatif, keputusan pembelian dan perilaku pasca pembelian. Penelitian ini menggunakan studi kasus terhadap kaos Uniqlo X BT21 dengan metodologi kualitatif. Hasil penelitian ini yaitu motivasi yang menyebabkan pembelian kaos Uniqlo X BT21. Interaksi parasosial terbukti mampu untuk mempengaruhi pembelian merchandise. Semakin lekat sebuah hubungan parasosial, maka akan semakin tinggi motivasi minat beli. Kolaborasi yang diadakan Uniqlo dengan BTS dapat dikatakan berhasil menarik minat penggemar. Sehingga kolaborasi merek dan public figure kini merupakan sebuah strategi yang dapat dilakukan untuk mempromosikan produk. Pebisnis perlu melihat peluang yang hadir dalam fenomena tersebut.